THE LEVEL AND COST BURDEN OF ABSENTEEISM AMONG HEALTH CARE PROFESSIONALS - Aysun Kandemir; Bayram Şahin (İşletme Bilimi Dergisi)
This study was aimed at identifying the prevalence of unscheduled absenteeism resulting in loss of labor among healthcare professionals and its cost burden on hospitals. The study was conducted with the participation of 951 hospital employees that comprised the doctors, nurses/midwives, other healthcare professionals and administrative staff employed at two different hospitals in Turkey. ‘Health and Work Performance Questionnaire (HPQ)’ developed by Kessler et al. (2003) was used as the data collection tool. The results indicated greater absenteeism in healthcare professionals aged 30 and under, married employees, female employees, nurses/midwives, university hospital staff and employees with a maximum of 5 years of service. The unscheduled absences and the cost of absenteeism were calculated as 11.52 days and 2372.46 TRY per employee per year. The study results emphasised the significance of unscheduled absenteeism in hospitals and its financial consequences. Hospital administrators could develop effective solutions by analysing the underlying causes.